Sevoflurane: Its action on heme metabolism and phase i drug metabolizing system - Sampayo, R; Lavandera, J V; Batlle, A; Buzaleh, A M (Cellular and Molecular Biology, 2009)
Acute attacks of porphyria are most commonly precipitated by events that decrease heme concentrations. Enzyme inducing-drugs are the most important triggering factors, particularly in relation to anaesthesia. We have reported previously that Enflurane and Isoflurane produced significant heme metabolism alterations, indicating that the use of these anaesthetics in porphyric patients should be avoided. The aim of this work was to evaluate the effect of the anaesthetic Sevoflurane on heme pathway and drug metabolizing Phase I system in mice. To this end, animals received different doses of the anaesthetic (1-2 ml/kg) and were sacrificed at different times (5-60 min). Data revealed important alterations in the enzymes involved in Acute Intermittent Porphyria, such as an induction in hepatic 5-Aminolevulinic acid synthetase activity and a diminished Porphobilinogen deaminase activity in liver and blood 20 minutes after Sevoflurane administration to mice in a dose of 1.5 ml/kg. Heme oxygenase activity was also induced, indicating the onset of oxidative stress. Total CYP levels and CYP2E1 expression were enhanced. As a consequence of these events, heme free pool would be depleted. In conclusion, our results in mice would suggest that Sevoflurane should be used with caution and very careful control in porphyric patients.